The relative importance of the bacterial pathway and soil inorganic nitrogen increase across an extreme wood‐ash application gradient. Issue 5 (5th January 2018) - Vestergård, Mette; Bang‐Andreasen, Toke; Buss, Sebastian Micki; Cruz‐Paredes, Carla; Bentzon‐Tilia, Sara; Ekelund, Flemming; Kjøller, Rasmus; Hindborg Mortensen, Louise; Rønn, Regin
Abstract: Ash from combustion of biofuels, for example wood chips, is often deposited as waste, but due to its high content of essential plant nutrients and alkalinity, it has been proposed to recycle ash as a fertilizer and liming agent in biofuel production forest. However, current legislation sets rather strict limitations for wood‐ash application in biofuel production systems. The soil microfood web, that is microorganisms and their microfaunal grazers, protozoa and nematodes, is pivotal for essential ecosystem processes such as decomposition and plant nutrient release. Therefore, a thorough assessment of the impacts on microfood web structure and functioning must precede actions towards raising the currently allowed application rates. In a Danish Norway spruce plantation, we evaluate the impact of wood ash applied at dosages from 0 to the extreme case of 90 t ash ha −1 on the microfood web, the bacterial community structure, soil content of inorganic nitrogen, organic matter, dissolved organic carbon and nitrogen. Using structural equation modelling (SEM), we disentangled the direct effect of the disturbance imposed by ash per se, the associated pH increase and changes in prey abundance on individual organism groups in the microfood web. The SEM showed that the pH rise was the main driver of increasing abundances of culturable heterotrophic bacteria with increasing ash doses, and via trophical transfer, this also manifested as higher abundances of bacterial grazers. Fungal‐feeding nematodes were unaffected by ash, whereas carnivorous/omnivorous nematodes decreased due to the direct effect of ash. Increasing ash doses enhanced the difference between bacterial communities of control plots and ash‐amended plots. The ash‐induced stimulation of culturable heterotrophic bacteria and bacterial grazers increased inorganic nitrogen availability at ash doses of 9 t ha −1 and above. Hence, raised limits for ash application may potentially benefit tree growth via enhanced N mineralization activity of the soil food web. Abstract : Structural equation model of effects of wood ash application doses on soil pH and soil organisms.